Biogas dry reforming over Ni-La-Ti catalysts for synthesis gas production: Effects of preparation method and biogas composition. (15th August 2023) - Veiga, Santiago; Romero, Mariano; Faccio, Ricardo; Segobia, Darío; Apesteguía, Carlos; Laura Pérez, Ana; Dante Brondino, Carlos; Bussi, Juan
Graphical abstract: Highlights: Ni-La-Ti was synthesized by 3 methods to explore structure–activity relationship. Preparation methods of Ni-La-Ti catalyst affect to the metal and support interaction. Modified Pechini synthesized catalyst showed highest degree of interaction. Modified Pechini catalyst exhibited better stability in dry reforming of biogas. Abstract: Biogas upgrading through dry reforming is a promising technology for converting biomass into high-value products such as synthesis gas. In this work, Ni-La-Ti catalysts were synthesized using different preparation methods (impregnation, coprecipitation and modified Pechini method) and evaluated in clean biogas dry reforming reaction at 800 °C using two different CH4 /CO2 molar ratios (1.5 and 3) to study the effects of the different biogas qualities on catalytic activity and stability. Fresh and used catalysts were examined by several techniques including the BET method, XRD, ICP-AES, H2 -TPR, CO2 -TPD, EPR, Raman, TGA, SEM and TEM. The different catalytic activities obtained could be attributed to the different degree of Ni-La-Ti interaction. The catalyst prepared by impregnation shows the highest initial catalytic activity for the two CH4 /CO2 ratios tested. However, it was observed that the formation of solid carbon took place to a greater extent on this catalyst. The catalyst prepared by the modified Pechini method showed good stability through a 100 h stability test using CH4 /CO2 = 1.5 feed ratio. Characterization of the used catalyst confirmed the formation of mainly filamentous type carbon and high resistance to Ni sintering.